2018
DOI: 10.2214/ajr.17.19074
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Approach to Prediction of Occult Mediastinal Lymph Node Metastasis of Lung Adenocarcinoma

Abstract: The radiomics signature of a primary tumor based on CT scans can be used for quantitative and noninvasive prediction of occult mediastinal LN metastasis of lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 22 publications
1
80
0
Order By: Relevance
“…Radiomics method was also applied in other imaging modalities like CT or MRI images of some primary cancer like bladder, colon cancer to predict regional lymph-node metastasis, demonstrating this method was a useful way to make a prediction of lymph-node metastasis 41,42 . Compared with the previous study, our study yielded a better diagnostic performance by concentrating on the clinical parameter combined DLR method, which can complement image features with more information and make the model more robust by restraining the features extracted from images 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics method was also applied in other imaging modalities like CT or MRI images of some primary cancer like bladder, colon cancer to predict regional lymph-node metastasis, demonstrating this method was a useful way to make a prediction of lymph-node metastasis 41,42 . Compared with the previous study, our study yielded a better diagnostic performance by concentrating on the clinical parameter combined DLR method, which can complement image features with more information and make the model more robust by restraining the features extracted from images 26 .…”
Section: Discussionmentioning
confidence: 99%
“…(6) The ROI included bronchi, blood vessels, and vacuoles within the nodules, excluding normal lung tissue. Previous studies [16][17][18] had reported that the radiomic analyses were capable of predicting the LNM in the patients with lung adenocarcinoma. The predicative AUC values based on the radiomic analyses regarding the patients who had both pre-surgical node-positive and node-negative in the CT scans were 0.86 from 159 patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…A few retrospective studies established that radiomic analyses could predict LNM using CT scans in both pre-surgically node-positive and node-negative lung adenocarcinoma patients [16][17][18]. We have used only the pre-surgical CT-based stage IA (imaging node-negative) NSCLC patients to predict LNM in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, predicting metastasis with machine learning algorithms, as a promising alternative for other invasive or noninvasive diagnostic method, has been proven to be feasible in lung adenocarcinoma and colorectal cancer [11,12]. These studies predicted on CT image and histologic evidence and obtained satisfying results.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing to traditional statistical models, ML predictive analysis has several bene ts, including less outcomes required for each predictor, no requirement for speci c hypothesis and allowance of interaction between variables [9,10]. ML-based predictive analysis has been validly used in medical eld [11,12]. From the authors' perspective, there were very few studies that have reported the application of ML algorithms for evaluating the risk of LNM in lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%